Amino acids trigger down-regulation of superoxide via TORC pathway in the midgut of Rhodnius prolixus. Issue 2 (15th April 2016) - Gandara, Ana Caroline P.; Oliveira, José Henrique M.; Nunes, Rodrigo D.; Goncalves, Renata L.S.; Dias, Felipe A.; Hecht, Fabio; Fernandes, Denise C.; Genta, Fernando A.; Laurindo, Francisco R.M.; Oliveira, Marcus F.; Oliveira, Pedro L.
Abstract : Rhodnius prolixus midgut redox balance is regulated by a signalling pathway involving amino-acids/TORC/mitochondrial ROS to protect the midgut from oxidative damage. Abstract : Sensing incoming nutrients is an important and critical event for intestinal cells to sustain life of the whole organism. The TORC is a major protein complex involved in monitoring the nutritional status and is activated by elevated amino acid concentrations. An important feature of haematophagy is that huge amounts of blood are ingested in a single meal, which results in the release of large quantities of amino acids, together with the haemoglobin prosthetic group, haem, which decomposes hydroperoxides and propagates oxygen-derived free radicals. Our previous studies demonstrated that reactive oxygen species (ROS) levels were diminished in the mitochondria and midgut of the Dengue fever mosquito, Aedes aegypti, immediately after a blood meal. We proposed that this mechanism serves to avoid oxidative damage that would otherwise be induced by haem following a blood meal. Studies also performed in mosquitoes have shown that blood or amino acids controls protein synthesis through TORC activation. It was already proposed, in different models, a link between ROS and TOR, however, little is known about TOR signalling in insect midgut nor about the involvement of ROS in this pathway. Here, we studied the effect of a blood meal on ROS production in the midgut of Rhodnius prolixus . We observed that blood meal amino acids decreased ROS levels in the R. prolixus midgut immediately after feeding, via lowering mitochondrial superoxide production and involving the amino acid-sensing TORC pathway.